Relaxin-like peptides in male reproduction: a human perspective - Ivell, Richard; Agoulnik, Alexander I.; Anand-Ivell, Ravinder (Wiley, 2017)
The relaxin family of peptide hormones and their cognate GPCRs are becoming physiologically well-characterized in the cardiovascular system and particularly in female reproductive processes. Much less is known about the physiology and pharmacology of these peptides in male reproduction, particularly as regards humans. H2-relaxin is involved in prostate function and growth, while insulin-like peptide 3 (INSL3) is a major product of the testicular Leydig cells and, in the adult, appears to modulate steroidogenesis and germ cell survival. In the fetus, INSL3 is a key hormone expressed shortly after sex determination and is responsible for the first transabdominal phase of testicular descent. Importantly, INSL3 is becoming a very useful constitutive biomarker reflecting both fetal and post-natal development. Nothing is known about roles for INSL4 in male reproduction and only very little about relaxin-3, which is mostly considered as a brain peptide, or INSL5. The former is expressed at very low levels in the testes, but has no known physiology there, whereas the INSL5 knockout mouse does exhibit a testicular phenotype with mild effects on spermatogenesis,probably due to a disruption of glucose homeostasis. INSL6 is a major product of male germ cells, although it is relatively unexplored with regard to its physiology or pharmacology, except that in mice disruption of the INSL6 gene leads to a disruption of spermatogenesis. Clinically, relaxin analogues may be useful in the control of prostate cancer, and both relaxin and INSL3 have been considered as sperm adjuvants for in vitro fertilization.